Fair Use Prevails in Oracle v. Google. - Samuelson, Pamela (Communications of the ACM, 2016)
The author discusses reasons why the computer software firm Oracle could lose its appeal to a jury's May 2016 rejection of its claim that the technology company Google infringed on its copyrights by using 37 packages of its Java application program interface (API) to develop the Android platform for smartphones. Topics include the U.S. fair-use defense, distinctions between Oracle's Java language and the Java API declarations, and Oracle's development of the Java API for a different computing environment.